Analysis of Information Quality, Trust and Satisfaction on Customer Participation (Case Study on Customer Online Shop Shopee In Rantauprapat) - Auliya Fadhillah; Yuniman Zebua; Yudi Prayoga (Budapest International Research and Critics University, 2021)
Online shopping can be accessed through digital applications known as e-commerce applications. One of e-commerce the well-known in Indonesia is shopee. The main purpose of this research is to determine the factors that influence the variables of Information Quality, Trust, Satisfaction with Customer Participation in Shopee Online Shop Customers in Rantauprapat. This study uses non-probability sampling method with accidental sampling technique, and statistical data processing in the form of processing validity and reliability, normality testing, multiple linear regression, simultaneous test (F test), partial test (T test) and test coefficient of determination with the number of respondents as many as 100 customers. The results of this study indicate that partially Information Quality, Trust and Satisfaction have a significant effect on customer participation. Simultaneously, the variables of Information Quality, Trust and Satisfaction have an effect on Customer Participation in Shopee Online Shop Customers in Rantauprapat